1. The problem statement, all variables and given/known data Find solution for y'' + y' -2y = 2x with initial values of y(0) = 0, y'(0) = 1 2. Relevant equations I have found yc = c1*exp(-2x) + c2*exp(x), but finding yp is what I'm having trouble with... AND THEN I'm not so sure how to go about the initial value. 3. The attempt at a solution Ok, so my "reasonable assumption" : yp = Ax y'p = A y''p= 0 When I plug into equation, I get: 0 + A -2(Ax) = 2x... and that's where I'm stuck. Any insights?